The Role of INSTIKI Students in Preventing Cyberbullying Among Teenagers - Ade Putri Intan Sari; Marshanda Cindy Mirela; Happy Budyana Sari (Journal of Digital Law and Policy, 2023)
Nowadays, the rapid development of information technology can have both good and bad effects on society, including teenagers. Technological advances allow many people to access the internet quickly, share information, and exchange information between one person and another without having to meet each other face to face. The freedom to use social media can lead to various social media cases of abuse. Cyberbullying is one of the misuses of social media that has recently been encountered. Cyberbullying is one example of the negative impacts arising from rapid technological development. Cyberbullying is a disgraceful behavior committed by individuals repeatedly to others via the internet. The relevant articles of the Criminal Code regulating this cyberbullying offense are those listed in Chapter XVI concerning Insults, specifically Article 310 paragraphs (1) and (2), and the ITE Law article 27 paragraphs (3) of the ITE Law. If there is no action to prevent or stop cyberbullying, then it could be that this action will increase and be very detrimental, especially for victims. This study aims to determine the role of INSTIKI students in preventing cyberbullying that occurs among teenagers. This research uses a mixed method, a combined method between quantitative and qualitative with the help of questionnaires in data collection. In this study, researchers distributed questionnaires online via a Google form. From the results of the questionnaire conducted, it shows that students play a role in preventing cyberbullying among teenagers, in this role, not a few students agree that holding socialization (seminars or counseling) is one of the best ways to prevent cyberbullying among teenagers. Socialization is given to teenagers to increase their understanding of the dangers and impacts of cyberbullying.